the Evaluation of the Implementation of Student Sports Education and Training Center (PPLP), North Sumatra - Amnas, Thova Amnas; Hartanto, Mugiyo; Kusuma, Donny Wira Yudha (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
This study analyzed a program, specifically the antecedents, transactions, and outcomes of a North Sumatra student sports education and development program (PPLP). The researchers employ the Countenance Evaluation Model (Stake) in terms of antecedents, transactions, and outcomes, which may be viewed as obtaining accurate and objective information and comparing the results of the accomplishment coaching program. The study collected data through observation, interviews, and documentation obtained from coaches, administrators, athletes, and members of the community. Analytical, presentation, and conclusion-drawing techniques. The findings of this study establish the antecedents of the coaching program, which has been shown to significantly improve the PPLP’s athletes achievement. While the training program for North Sumatra PPLP athletes has been going well, the transaction has not gone well. As a result, the North Sumatra PPLP achievement development program has been carried out in the city of Medan. All sports have seen a decrease. As a result, antecedents in PPLP North Sumatra have clear and directed management, human resources, facilities and infrastructure, funding, and training programs. While the majority of the transactions in the PPLP North Sumatra development program are deemed to be favorable, there are still some that fall short of implementation. The outcome in this situation is not favorable. In all sports, the athlete’s own success is less stable, resulting in a decrease in achievement.